A study on impact of national rural employment guarantee program in Thiruvannamalai district, Tamil Nadu, India during the period from 1997-2007 - Palanichamy, A.P. (International Multidisciplinary Research Journal, 2011)
Rural development is defined as structural change in the socio-economic situation to achieve improved living standard of low income population residing in rural areas and making the process of their development self-sustaining. It includes economics development with close integration among various sectors, and economic growth specifically directed at the rural poor. In India, the number of unemployed people has grown by more than four times in 10 years from 10.8 million in 1991 to 44.5 milion in 2001, which was only 5.3 million in the beginning of the economic planning. The average annual employment has increased from pre programme periods to the post programme periods. In Azhaganandal the average employment was 728 mandays in the pre-programme periods. The average annual employment has increased from 634 man days in the pre-programme periods to 1390 mandays in the post programme periods in Kannapandal. As regards Nallanpillai pettral. The average annual employment was 860 mandays in the pre-programme periods and it has increased to 1638 mandays in the post programme period.